Use of REBOA as a Bridge to Endovascular Aortic Repair in Blunt Abdominal Aortic Injury - Chiarini, V; Coniglio, C; Ferri , E; Lupi , C; Tugnoli, G; Montanari, N; Gordini , G (Journal of Endovascular Resuscitation and Trauma Management, 2019)
Blunt abdominal aortic injury (BAAI) is a rare but challenging traumatic lesion. Since BAAI is difficult to suspect and diagnose, frequently lethal, and associated to multiorgan injuries, its management is objective of research and discussion. Resuscitative endovascular balloon occlusion of the aorta (REBOA) is an accepted practice in ruptured abdominal aortic aneurysm. Conversely, blunt aortic injuries are the currently most cited contraindications for the use of REBOA in trauma, together with thoracic lesions. We report a case of BAAI safely managed in our Trauma Center at Maggiore Hospital in Bologna (Italy) utilizing REBOA as a bridge to endovascular repair, since there were no imminent indications for laparotomy. Despite general contraindication to blindly placing REBOA in aortic rupture, we hypothesize that a multidisciplinary approach, involving endovascular specialists able to exclude the lesion with the balloon, could be feasible and relatively safe when introduced in a resuscitative damage control protocol.